The Development and Assessment of a Flipped Classroom Instructional Plan and Its Effect on Students’ Motivation and Engagement - Kamarzaman, Intan Haslina; Yahaya, Rusliza; Yusof, Rohaila (International Business Education Journal, 2022)
This study intended to build a flipped classroom instructional plan for four Management Accounting subjects in matriculation institutions and test its effect on students’ motivation and engagement. The instructional plan’s content and learning activities were based on the Malaysian Ministry of Education’s Matriculation Curriculum Specifications and the First Principle of Instruction. In the first phase, three experts verified the instructional plan draught. The Percentage Calculation Method indicated overall content validity was 93.3%. Based on comments and ideas from experts, several changes and improvements were made to build the most acceptable and appropriate instructional plan for matriculation college. In the second phase, a quasi-experiment was conducted with 80 accounting students enrolled in the Management Accounting course. Students were divided into experimental and control groups. The experimental group was taught using a flipped classroom technique, whereas the control group was taught using a traditional method. According to the t-test result, flipped classroom students demonstrated a significantly higher motivation and engagement than traditional group students. The findings suggest a flipped classroom instructional plan may increase student motivation and engagement.